From humor to horror: genre and narrative purpose in abortion stories on American television. Issue 2 (17th February 2019) - Sisson, Gretchen
Abstract: A recent increase in the number of comedic films and television programs that include abortion stories has prompted a cultural conversation about whether this is an appropriate treatment for such a topic: Can abortions be funny? Are there any genres that should not include plotlines about abortion? Indeed, most prior examinations of abortion on television have focused on dramas and their impact, without explicitly exploring the ways different genres offer a range of types of stories and creative opportunities. Using a comprehensive data-set of abortion plotlines on American television, this analysis provides a historical overview of how varying genres have addressed abortion in the past, as well as closer case studies within each of five genres: drama, soap opera, horror, science fiction, and comedy. This paper provides insight into the different narrative functions of abortion stories, with consideration of how such narratives support (in)accurate and (de)stigmatizing cultural ideas about abortion.